2013
DOI: 10.1007/s00432-013-1393-5
|View full text |Cite
|
Sign up to set email alerts
|

Frequent promoter hypermethylation of tachykinin-1 and tachykinin receptor type 1 is a potential biomarker for head and neck cancer

Abstract: CpG hypermethylation is a likely mechanism of TAC1 and TACR1 gene inactivation, supporting the hypothesis that TAC1 and TACR1 play a role in the tumorigenesis of HNSCC and that this hypermethylation may serve as an important biomarker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 33 publications
0
32
0
Order By: Relevance
“…Such knowledge could carry importance in a clinical setting, for example, to predict either prognosis and/or a treatment response with NK1R antagonists. Such a correlation has been described for the expression rate of the SP/NK1R complex and prognosis in other pediatric tumors (110,(152)(153)(154). For example, Garcia-Recio et al found that SP contributes to persistent transmodulation of the ErbB receptors, EGFR and HER2, in breast cancer, where it enhances malignancy and therapeutic resistance (110).…”
Section: The Nk1r As An Anti-tumor Target In Hepatoblastoma In the CLmentioning
confidence: 85%
“…Such knowledge could carry importance in a clinical setting, for example, to predict either prognosis and/or a treatment response with NK1R antagonists. Such a correlation has been described for the expression rate of the SP/NK1R complex and prognosis in other pediatric tumors (110,(152)(153)(154). For example, Garcia-Recio et al found that SP contributes to persistent transmodulation of the ErbB receptors, EGFR and HER2, in breast cancer, where it enhances malignancy and therapeutic resistance (110).…”
Section: The Nk1r As An Anti-tumor Target In Hepatoblastoma In the CLmentioning
confidence: 85%
“…It has previously been proposed that a correlation exists between the expression rate of the NK1R/SP complex and prognosis in various types of cancer (18)(19)(20)(21)(22). Garcia-Recio et al identified that SP contributes to persistent transmodulation of the ErbB receptors, epidermal growth factor receptor (EGFR) and human epidermal growth factor 2 (HER2), in breast cancer, acting to enhance malignancy and therapeutic resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, this signature discriminates invasive and metastatic from localized HB and predicts prognosis with high accuracy (16). Additionally, it has recently been suggested that the expression of TACR1 may correlate with a clinically worse prognosis in some cancers (18)(19)(20)(21)(22). However, scientific evidence for such an association remains scarce.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, data from our laboratory have shown that the galanin , GALR1 , GALR2 , TAC1 , and TACR1 promoters are methylated in HNSCC. [15,16] Therefore, we hypothesized that neuropeptide genes and receptor genes might be inactivated via promoter hypermethylation in human head and neck cancers, and that hypermethylation of these genes is an important event in the genesis of HNSCC. Moreover, we discovered a unique inverse relationship between SST and SSTR1 -promoter hypermethylation and other neuropeptide genes.…”
Section: Introductionmentioning
confidence: 99%